(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1990)
The Carnian sedimentary succession of the Lierna area, more than 4OO m thick and belonging to the Coltignone tectonic unit (Grigne Group), has considerable paleogeographic significance, for it documents the western termination of the deltalagoon-carbonate platform depositional system of the Lombard Prealps. The Carnian succession, directly overlying basinal (Perledo-Varenna Formation) to shallow-marine (Lierna Formation) carbonates of Ladinian age, is characterized by deltaic terrigenous deposits (Val Sabbia Sandstone), progressively replaced by lagoonal (Gorno Formation) to peritidal (Breno Formation) limestones. In the studied stratigraphic sections these three lithofacies alternate vertically at decametric scale, and are each characterized by different types of cyclothems at metric scale. High-frequency "punctuated aggradational cycles" (PAC) are best recognized at the top of the Val Sabbia clastic body, where the final transition to the Gorno lagoon is marked by arenite layers containing ferruginous ooids. Grains of this type have nor been previously reported from Southalpine arenites. The petrographic composition of the Val Sabbia Sandstone points to provenance from an active volcanic chain, but abundance of quartzose detritus and occurrence of perthitic K-feldspar and sedimentary rock fragments suggest extensive erosion of the Hercynian basement and Upper Carboniferous to Ladinian sedimentary cover. These peculiar characteristics confirm the existence of a small "Lierna lobe" separated from the deltaic systems of central Lombardy, and fed by a basement- high located southwest of Como lake.